2019
DOI: 10.1111/pce.13689
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome and transcriptome analysis unravels key factors of nitrogen use efficiency in Brassica napus L

Abstract: Considerable genetic variation in agronomic nitrogen (N) use efficiency (NUE) has been reported among genotypes of Brassica napus. However, the physiological and molecular mechanisms underpinning these differences remain poorly understood. In this study, physiological and genetic factors impacting NUE were identified in field trials and hydroponic experiments using two B. napus genotypes with contrasting NUE. The results showed that the N‐efficient genotype (D4‐15) had greater N uptake and utilization efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 74 publications
(154 reference statements)
3
26
2
Order By: Relevance
“…5). What's more, recent research has identified the gene BnaA06g04560D (BnNRT2.1d) as a key factor in NUE through genomic and transcriptomic analysis experiments involving two Brassica napus genotypes contrasting in NUE [43]. Additionally, BnNRT2.5 expression profiles vary between seedlings and adult plants, though expression increased with decreases in external N supply (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5). What's more, recent research has identified the gene BnaA06g04560D (BnNRT2.1d) as a key factor in NUE through genomic and transcriptomic analysis experiments involving two Brassica napus genotypes contrasting in NUE [43]. Additionally, BnNRT2.5 expression profiles vary between seedlings and adult plants, though expression increased with decreases in external N supply (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds were soaked in deionized water in the dark for 2 days and subsequently transferred to a net floating on 0.5 mM CaCl 2 solution for 3 days. The seedlings were then grown in a nutrient solution (pH 5.8) according to our previous report [ 31 ]. The solution contained NH 4 NO 3 3.0 mM, NaH 2 PO 4 ·2H 2 O 1.0 mM, MgSO 4 ·7H 2 O 2.0 mM, KCl 2.0 mM, CaCl 2 3.24 mM, H 3 BO 3 46.0 μM, MnCl 2 ·4H 2 O 9.14 μM, Na 2 MoO 4 ·2H 2 O 0.5 μM, ZnSO 4 ·7H 2 O 0.77 μM, CuSO 4 ·5H 2 O 0.32 μM and EDTA-iron (Fe) 25.0 μM.…”
Section: Methodsmentioning
confidence: 99%
“…B. napus needs high amount of N to maintain normal growth and development, and is extremely susceptible to N deficiency. N shortage in the soil may inhibit the growth of B. napus , and its yield production and quality [ 30 , 31 ]. NPF families have been identified in various plant species, such as poplar [ 32 ], wheat [ 33 ], legumes [ 34 ], apple [ 35 ] and sugarcane [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that gene expression of plants changes during N starvation. There are some differences in gene expression between N-efficient and N-inefficient genotypes (Wang et al 2016;Li et al 2020). In the present study, the nitrogen use efficiency of 338 P. deltoides genotypes had been preliminarily evaluated, and the adaptability to N stress had also been analyzed.…”
Section: Morphological and Physiological Differences Among Genotypes With Different Nitrogen Use Efficienciesmentioning
confidence: 99%